Mid-term outcomes from a multicenter study: Is TEVAR safe for ascending aortic dissection?. (15th August 2018) - Lu, Qingsheng; Liu, Lei; Chang, Guangqi; Chen, Xueming; Feng, Hai; Zhang, Xuemin; Fu, Weiguo; Dong, Zhihui; Jing, Zaiping
Abstract: Objectives: This study aims to report mid-term follow-up outcomes of a series of TAAD patients treated with TEVAR in China. Background: Thoracic endovascular aortic repair (TEVAR) has been used to treat type A aortic dissection (TAAD) for years. However, by comparing public reports, their outcomes which were based on different sample sizes show inconsistency. Methods: Between January 2001 and December 2015, there were 56 patients with TAAD received TEVAR identified in 5 medical centers. The morphology changes and early and late outcomes were recorded and analyzed. Results: 56 patients (aged 38 to 80) with TAAD received TEVAR. The average follow-up period was 39.92 ± 34.42 months (ranging from 11 to 140 months). 54 (96.43%) cases were technically successful. 1 patient died on day 2 after TEVAR because of stent graft migration during the procedure. There were 7 early events (within 30 days), including sudden death (1), cerebral infarction (3), stent graft migration (1), new dissection (1) and respiratory failure (1). The 30-day overall survival rate was 92.9%. 27 late events occurred during the follow-up: retrograde dissection (8), endoleak (5), coronary artery stenosis (3), cerebral infarction (3), new dissection (2), multiple organ dysfunction syndrome (1), left ventricular pseudoaneurysm (1), stent graft migration (1), respiratory failure (1), supraventricular tachycardia (1) and pericardial effusion (1). The 5-year overall survival rate of this study was 80.9% and this rate reached 98.2% if aorta-related deaths were excluded. Conclusions: TEVAR could be an effective alternative for high-risk patients. However, issues resulted from postoperative complications still call for attention. Highlights: The technically successful rate of the TEVAR for TAAD reaches 96.43%. The 5-year overall survival rate was 80.9% and it reached 98.2% if aorta-related deaths were excluded. The complete thrombosis of false lumen in the ascending aorta achieves 100% at postoperative 12 month. There are a series of kinds of postoperative complications in the follow-up.